Tungiasis – A cause of painful feet in a tropical traveller - Hakeem, M.J.M.L.; Morris, Allen K.; Bhattacharyya, D.N.; Fox, Christopher (Travel medicine and infectious disease, 2010)
Tungiasis is an ectoparasitosis caused by the impregnated female sand flea Tunga penetrans. It is endemic in certain resource poor areas around the world and imported infestations in travellers can lead to considerable morbidity. With the rise in international travel and immigration, the likelihood of physicians encountering such tropical skin infestations is rising. The ability of physicians to recognise tungiasis early will be immensely beneficial to patients. We describe a case of tungiasis where a traveller presented with painful foot lesions. The patient had returned to the United Kingdom 4 days previously after spending 4 weeks in the Pantanal region in Brazil. A literature review on this subject was undertaken in this article.